Variability of Peronosclerospora sorghi isolates from different geographic locations and hosts in Africa - Bock, C.H.; Jeger, M.J.; Mughogho, L.K.; Cardwell, K.; Mtisi, E.; Kaula, G.; Mukansabimana, D. (2000)
Nine isolates of Peronosclerospora sorghi from maize, sorghum and wild sorghum were sampled from Zimbabwe, Zambia, Rwanda, Mozambique and Kenya. They were compared for variation in conidium and conidiophore morphology, temperature requirements for sporulation, germination and germ-tube growth and for pathogenicity on different sorghum and maize cultivars. Although there were significant differences in isolate morphology, all conformed to the known range for P. sorghi. Mean conidial length×width ranged from 21–23 μm×16•9–19•2 μm, and mean conidiophore length (basal cell-branching) ranged from 116•3–135•6 μm. All isolates sporulated in the range 14–26 °C (optimal at 16–23°), although one isolate from maize from Umbeluzi in Mozambique had a broader optimal range for sporulation (12–25°). Conidia of all isolates germinated between 10° and 34°. Germ-tube response to temperature was similar for all isolates (10–34°). The isolates varied in their pathogenicity towards sorghum cultivars, with an isolate from Rwanda being pathogenic to more sorghum differentials than any other. Cluster analysis of isolates based on host reaction indicated five groups at the 85% similarity level. The existence of pathogenic variability has ramifications for the breeding of sorghum for resistance to downy mildew in Africa.